PEGEMBANGAN SOFT SKILL FOTOGRAFI SEBAGAI ALAT KOMUNIKASI VISUAL YANG EFEKTIF DI SMA IBRAHIMY 1 SUKOREJO - Muhammad Robitul Umam; Arif Ferdiansyah; Zaehol Fatah (CV. Denasya Smart Publisher, 2025)
This study aims to examine the effectiveness of photography training as a medium for developing soft skills in the context of secondary education, especially at SMA Ibrahimy 1 Sukorejo. Photography was chosen because it is a form of visual communication that is able to convey messages in an explorative, creative, and contextual manner. Through a qualitative descriptive approach, this study observed the training process which includes four main stages, namely interactive lectures, technical photography training, field practice, and reflective discussions. These four stages are designed to build technical skills while instilling the values ​​of cooperation, interpersonal communication, critical thinking, and a sense of responsibility in the participants. The results of the observations showed that students experienced significant improvements in their ability to express ideas visually and work in groups collaboratively. Reflective discussions proved to be an effective space to train the courage to express opinions and the ability to receive feedback constructively. Field practice also built social sensitivity and the ability to see reality from various perspectives. This photography training succeeded in becoming an alternative learning medium that was both fun and meaningful. Not only did it improve visual competence, this activity also strengthened students' character and life skills. These findings indicate that the integration of creative activities such as photography is very relevant to be applied in character-based education efforts in the digital era.